(untitled) (Italian Journal of Public Health, 2009)
When Prof. Ricciardi shared with me the idea of passing the witness of the editorship of the Italian Journal of Public Health, we were walking in a beautiful square in Lisbon, where we were attending to the annual EUPHA meeting. It was a cloudy and humid night, and at that time I did not realise fully all the possible implications of this decision. Anyway, I accepted. It is a big honour for me to be the successor of Prof. Ricciardi as Editor in Chief of this journal, and this for several reasons, from the academic and personal points of view. In the last seven years, the Italian Journal of Public Health has been a sort of contradiction in terms. It is with no doubt an Italian journal, in which many contributions from all over Italy appeared. But it is also an international journal, not only because it is written in English, but also due to the fact that almost 40% of published papers come from outside Italy. The reason why this has happened is mainly due to our membership to EUPHA and to several scientific network (this issue is a practical explanation of this kind of activity), and I really thank all colleagues who so kindly send in their manuscripts.